2013
DOI: 10.1262/jrd.2012-114
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbic Acid Improves the Developmental Competence of Porcine Oocytes After Parthenogenetic Activation and Somatic Cell Nuclear Transplantation

Abstract: In this study, a dose-response assessment was performed to understand the relation between supplementation of media with L-ascorbic acid or vitamin C and porcine oocyte maturation and the in vitro development of parthenotes (PA) and handmade cloned (HMC) embryos. Various concentrations (0, 25, 50 and 100 µg/ml) of vitamin C supplemented in in vitro maturation (IVM) and culture (IVC) media were tested. None of these vitamin C additions affected nuclear maturation of oocytes, yet supplementation at 50 µg/ml led … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
58
2
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(70 citation statements)
references
References 52 publications
8
58
2
2
Order By: Relevance
“…Intracellular GSH levels were determined by previously reported methods [14,32]. Briefly, cell tracker blue CMF2HC (4-chloromethyl-6, 8-difluoro-7-hydroxycoumarin; Molecular probe, Life technology) was used to detect intracellular GSH level by blue fluorescence.…”
Section: Measurement Of Intracellular Glutathione (Gsh) Levelmentioning
confidence: 99%
“…Intracellular GSH levels were determined by previously reported methods [14,32]. Briefly, cell tracker blue CMF2HC (4-chloromethyl-6, 8-difluoro-7-hydroxycoumarin; Molecular probe, Life technology) was used to detect intracellular GSH level by blue fluorescence.…”
Section: Measurement Of Intracellular Glutathione (Gsh) Levelmentioning
confidence: 99%
“…It was shown that the optimum concentration of vitamin C was 50 µg/mL during IVM of porcine oocytes [20], this concentration not only improved blastocyst rates, total cell numbers but also, reduced apoptotic indices and the high concentration (100 µg/mL) of vitamin C induced high apoptotic index. Miclea [21] and Huang [22] mentioned that the treatment with 50 µg/mL vitamin C resulted in increasing pregnancy rate and enhancing the development somatic cell nuclear transfer embryos in pigs.…”
Section: Discussionmentioning
confidence: 95%
“…The beneficial effect of vitamin C addition might be a scribed to an improved the culture condition and oocytes cytoplasmic maturation by reduction the intra cellular oxidative status for embryo development [7,20]. Moreover, Eppig [24] and Wang [6] mentioned that the addition of ascorbic acid into the culture media prevented follicular apoptosis in rat and mouse follicles, and also improved the blastocyst production.…”
Section: Discussionmentioning
confidence: 99%
“…But supplementation of 50 μg/mL led to significantly increased intracellular glutathione levels and reduced ROS and improved cleavage rates, blastocyst rates and total cell numbers per blastocyst. Also supplementation with 50 μg/mL vitamin C decreased the apoptosis index as compared with the groups supplemented with 100 μg/mL (19). Barzegari Firouzabadi's study which investigated the effects of ascorbic acid on the IVM of mouse's follicles and enclosed oocytes mentioned that ascorbic acid could increase survival rate but did not affect diameter, GV breakdown, and oocyte maturation rates (22).…”
Section: Discussionmentioning
confidence: 99%